Constituent Acids of Cucumis sativus Fruit Cutin - Dan (Nee Datta), J.; Thakur, S. (Asian Journal of Chemistry, 2010)
The cutin from fruit peel of Cucumis sativus was found to constitute n-alkanoic (C12—C36), α, ω-alkandioic (C9,C16,C18 and C22) hydroxyalkanoic (C14—C23), hydroxy α, ω-alkandioic (C12—C32) and benzoic acid together with hippuric acid. The main constituents were octadecandioic acids (ca. 13%), 8,10-dihydroxy octadecandioic acid (ca. 11 %) and octadecendioic acid (ca. 10%).